Genomic approaches to understand the genetic response to Phytophthora cinnamomi Rands in Castanea spp. - Santos, Carmen Sofia Pedro dos (2019)
"Chestnut is a multipurpose tree, having important economic, ecological and scientific values. European chestnut (Castanea sativa) produces the most appreciated and valued nuts worldwide. However, chestnut orchards and forests are declining in Europe due to introduced diseases and pests, mainly the ink disease. This destructive disease is caused by the widespread soil-borne oomycete Phytophthora cinnamomi. P. cinnamomi infection occurs in roots causing root rot and dieback in susceptible species. Nevertheless, the susceptible level varies among chestnut species, being the Asian species the most resistant to the pathogen.(...)"